Current Trends in the Evaluation of Osteochondral Lesion Treatments: Histology, Histomorphometry, and Biomechanics in Preclinical Models. (9th October 2019) - Maglio, M.; Brogini, S.; Pagani, S.; Giavaresi, G.; Tschon, M.
Abstract : Osteochondral lesions (OCs) are typically of traumatic origins but are also caused by degenerative conditions, in primis osteoarthritis (OA). On the other side, OC lesions themselves, getting worse over time, can lead to OA, indicating that chondral and OC defects represent a risk factor for the onset of the pathology. Many animal models have been set up for years for the study of OC regeneration, being successfully employed to test different treatment strategies, from biomaterials and cells to physical and biological adjuvant therapies. These studies rely on a plethora of post-explant investigations ranging from histological and histomorphometric analyses to biomechanical ones. The present review aims to analyze the methods employed for the evaluation of OC treatments in each animal model by screening literature data within the last 10 years. According to the selected research criteria performed in two databases, 60 works were included. Data revealed that lapine (50% of studies) and ovine (23% of studies) models are predominant, and knee joints are the most used anatomical locations for creating OC defects. Analyses are mostly conducted on paraffin-embedded samples in order to perform histological/histomorphometric analyses by applying semiquantitative scoring systems and on fresh samples in order to perform biomechanical investigations by indentation tests on articular cartilage. Instead, a great heterogeneity is pointed out in terms of OC defect dimensions and animal's age. The choice of experimental times is generally adequate for the animal models adopted, although few studies adopt very long experimental times. Improvements in data reporting and in standardization of protocols would be desirable for a better comparison of results and for ethical reasons related to appropriate and successful animal experimentation.